The Need For Economic Doctrine HR (HR Concept Identification Of HR Values, Supply And Demand For Manpower And Characteristics Of Educated Personnel, HR Development Efforts) - Pirmanuddin, Pirmanuddin; Kasful Anwar US; As'ad Isma (Cita konsultindo, 2023)
Human resources are the potential contained in humans to realize their role as adaptive and transformative social beings who are able to manage themselves and all the potential contained in nature towards achieving life welfare in a balanced and sustainable order. Human resource management (HRM) talks about how to design a management system to ensure that human talent is used effectively and efficiently to achieve organizational goals. Humans are the core competence in the organization. Human Resources (HR) or human resources contain two meanings. First, HR implies work effort or services that can be provided in the production process. Second, HR concerns humans who are able to provide services or work effort. Being able to work means being able to carry out activities that have economic value, namely that these activities produce goods or services to meet the needs of society. Physically, the ability to work is measured by age. In other words, people of working age are called labor or man power. The bigger the challenge. Starting from the compatibility of the skills obtained, the demands of the world of work, now the links and matches have not been built. Many educational institutions may still use a curriculum that industry may no longer use,